25-OH Vitamin D Levels and Cognitive Performance: Longitudinal Assessment in a Healthy Aging Cohort - Carvalho, André Couto; Santos, Nadine Correia; Portugal-Nunes, Carlos; Castanho, Teresa Costa; Moreira, Pedro; Costa, Patrício Soares; Sousa, Nuno; Palha, Joana Almeida (Frontiers in Aging Neuroscience, 2019)
Background: Declining serum levels of 25-hydroxyvitamin D [25(OH)D, a biomarker of vitamin D status] with aging is a well-recognized phenomenon. However, scarce information is available on the relation between 25(OH)D levels and cognitive performance over time in older individuals. Our purpose was to evaluate, longitudinally, the association of 25(OH)D with cognitive function in a healthy older adults’ cohort. Methods: Sixty-four individuals over 55 years-old with no cognitive impairment, clustered as healthy “Poor” and “Good” cognitive performers, were followed for an average of 18 months. Seasonal-adjusted 25(OH)D serum levels (measured by high-performance liquid chromatography-tandem mass spectrometry) were related, longitudinally, with cognitive (memory and general/executive) composite scores. Results: Overall seasonal-adjusted median serum 25(OH)D level was of 47 nmol/l [interquartile range (IQR), 38-60 nmol/l]. A negative correlation between baseline 25(OH)D and the general/executive composite score was found in the “Poor” cognitive performers (rs=-0.52, p=0.006), an association lost after adjusting 25(OH)D levels for the season. No effect was found in both groups between seasonal-adjusted 25(OH)D levels and the variation of both memory and general/executive composites during follow-up when adjusted for age, gender and education level. Conclusion: In this healthy older population with no cognitive impairment, lower serum levels of 25(OH)D were not longitudinally associated with poorer cognitive scores.